Menyusui Setelah Kembali Bekerja: Sistematik Review - Siti Nurjanah; Riadini Wahyu Utami (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
The work of the mother is cited as a major potential obstacle in exclusive breastfeedingand is a factor that can reduce the duration of breastfeeding. The time the motherreturns to work has an impact on the duration of breastfeeding. This study usedsystematic review where a systematic review was conducted following a combinationof preferred reporting items for systematic review and meta-analysis (PRISMA). Thedatabase uses ScienceDirect, SpringerLink, CINAHL, ProQuest, SAGE journals, andPubMed). Based on the results of the article search, 15 selected articles related tobreastfeeding mothers returning to work were obtained. The prevalence of exclusivebreastfeeding was 75.7%. Have a short period of maternity leave (AOR 9.3; 95%CI3.8, 23), be a full-time employee (AOR 3.5;95% CI 1,7,11), be a private employee(AOR 2.1), less flexible working time (AOR 3.0 95% CI 1.2) do not pump breast milk(AOR 4.3 95%CI 1.7, 11), lack of breastfeeding rest rest (AOR 6.7;95% CI 3,14,5) anda workplace away from her child (AOR 3.1;95% CI 3.1, 6.3) significantly associatedwith the cessation of EBF among working mother. The conclusion of this research is That maintaining breastfeeding requires time and commitment from the mother, as wellas a supportive workplace or learning environment.Keywords: breastfeeding, work, systematic review